2024
DOI: 10.3390/jcm13123361
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of microRNAs and Their Involvement in Recurrent Pregnancy Loss

Maria-Markella Patronia,
Anastasios Potiris,
Despoina Mavrogianni
et al.

Abstract: Background: Recurrent pregnancy loss refers to the spontaneous demise of two or more pregnancies before the 24 weeks of gestation. In almost half of the cases of recurrent miscarriages, the causes remain unknown since there is no reliable way of prognosis, early diagnosis, or treatment. Recent research has detected differential expression of certain miRNAs in reproductive system pathologies. Methods: The aim of the present review is to focus on microRNAs and their relationship with idiopathic recurrent miscarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…MicroRNAs (miRNAs) are endogenous non-coding small RNA molecules, about 22 nucleotides in length, that regulate more than 60% of protein-coding human RNA by either regulating gene expression or degrading mRNA. MiRNAs play a crucial role in various regulatory biological processes, and alterations in their expression are linked to the development of many diseases, including RPL [ 19 , 20 ]. Several recent studies have reported the differential expression of specific miRNAs in RPL [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are endogenous non-coding small RNA molecules, about 22 nucleotides in length, that regulate more than 60% of protein-coding human RNA by either regulating gene expression or degrading mRNA. MiRNAs play a crucial role in various regulatory biological processes, and alterations in their expression are linked to the development of many diseases, including RPL [ 19 , 20 ]. Several recent studies have reported the differential expression of specific miRNAs in RPL [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported the differential expression of specific miRNAs in RPL [ 21 , 22 , 23 , 24 , 25 ]. A systematic review of 21 studies by Patronia et al identified 75 statistically significant differentially expressed miRNAs (DEMs) in women affected by RPL, including miR-184, miR-520, miR-155/-5p, miR-100-5p, miR-146a/-5p, miR-21, miR-23a-3p, miR-92a/-3p, and miR-221-3p [ 19 ]. However, no comprehensive research has been conducted on paternal miRNAs in this context.…”
Section: Introductionmentioning
confidence: 99%